Perfil socio demográfico e clinico dos usuários hipertensos, matriculados no Programa de Controle da Hipertensão na Vila Santo Antônio do Prata no Município de Igarapé-Açu: a hanseníase nesse contexto - VILHENA, Bruno Albuquerque (2020)
Systemic Arterial Hypertension-SAH or high blood pressure is a chronic disease characterized by high blood pressure levels in the arteries. From the analysis of the new lifestyle of Brazilians it is possible to understand the need for the development of primary care programs aimed at the prevention, identification and monitoring of cases of hypertension. The construction of this work will bring the opportunity to instruct health professionals working in primary care to use the information collected about patients in control of systemic arterial hypertension enrolled in the hyperdia program, as a possible tool for better control of care for hypertensive patients. Basic is the entrance of patients in the single health system being hypertensive patients, welcomed with a standard care routine that seeks to identify the degree of hypertension to start treatment, according to the need of each situation. Quantitative, documentary, analytical and cross-sectional study, conducted with data from medical records of hypertensive patients enrolled in the Hiperdia Program at the UBS of Vila Santo Antônio do Prata in the municipality of Igarapé Açu. These data were analyzed from the construction of tables using the Excel program. According to the risk factors and blood pressure values obtained from the medical records of patients participating in the hyperdia program at the basic health unit of Vila Santo Antônio do Prata in the municipality of Igarápe-Açú, the degree of risk was identified. During the medical records research, hypertensive patients with a history of leprosy treatment were identified, which is a chronic condition that contributes to the occurrence of different mortality patterns in the country, largely related to chronic degenerative conditions and their complications.